Serine ether glycerophospholipids: Decrements in the frontal cortex associated with mild cognitive impairment and Alzheimer’s disease - Wood, Paul L.; Woltjer, Randall L. (Frontiers in Aging Neuroscience, 2022)
Ether glycerophospholipids (GPL) are involved in membrane fluidity and fusion. Vinyl-ether GPL are also conjectured to provide antioxidant capacity in the brain. The roles of these lipids in the processes involved in the development of dementia are not understood but choline and ethanolamine vinyl-ether GPL (i.e. plasmalogens) are decreased in the brains of subjects with dementia. In contrast, serine ether and vinyl-ether GPL have not been investigated in human brain. We therefore undertook an evaluation of these lipids, utilizing high-resolution mass spectrometry (HR-MS), in tissues from control and dementia subjects that we had previously characterized in-depth. We can report for the first time that a number of serine ether GPL and a more limited number of serine plasmalogens are present in human frontal cortex. In addition, we found that some of these frontal cortex lipids are decreased in Mild Cognitive Impairment (MCI), early-onset Alzheimer’s disease (EOAD), and late-onset AD (LOAD). In contrast no alterations in serine ether GPL were monitored in the frontal cortex of donors with schizophrenia, demonstrating disease specificity. These data suggest that further studies of the roles of ether GPL, including serine ether GPL, in brain function are worthy of undertaking.